Philosophical view on information theory (The path from the divine to the digital world) - Kazimi, Parviz Firudin Oqlu; Oqlu, İslamov İslam Ahmedaqa; Qizi, Yusifova Gulnare Yusif (Technium Social Sciences Journal, 2022)
Thoughts about the divine origin of information resurfaced in the 21st century and were called the information age. The views of ancient and medieval thinkers on information are more like mystical and romantic interpretations. Scientists of the twentieth century tried to interpret information more fully by materializing it. Thus, the study of information technology, information and communication technologies and their intensive application in our daily lives have made this area extremely relevant. Sometimes it is difficult for experts who ask "what's going on" to understand the nature of global information. It is important to take a closer look at the object as part of a philosophical review of the theories put forward about the definition of information and its configuration. This article can be considered a step in that direction.